IDENTIFICATION AND NUTRITIVE VALUE OF POTENTIAL FODDER TREES AND SHRUBS IN THE MID RIFT VALLEY OF ETHIOPIA - B. Shenkute; A. Hassen; T. Assafa; N. Amen; A. Ebro (Journal of Animal and Plant Sciences, 2012)
The aim of this study was to identify potential browse species in the mid Rift Valley of Ethiopia and to assess their nutritive value. A total of 120 household from four districts in the mid Rift Valley of Ethiopia were interviewed to identify locally important browse species. Herbarium samples were collected for identification and/or confirmation of the scientific names. Samples were also taken for chemical composition analysis. A total of 18 different browse species were identified, which are regarded as being important for different classes of livestock. The CP value of the edible component ranged between 8.95-20.9%, the NDF values ranged from 30.41-78.55%, the ADF values ranged from 19.42-47.5%.,and the ADL values ranged from 7.16 to 24.68. Generally the differences in chemical composition between different browse species were significant. These results indicate that there is a number of promising browse species in the indigenous flora. However, apart from chemical composition, they need to be characterized further in terms of palatability, digestibility, feed intake, animal response trials and anti-nutritional factors, in order to be able to enhance their utilization in the future.
Keywords: Mid rift valley browses; chemical composition; and nutritive value.